MANAJEMEN RISIKO LIKUIDITAS BANK PERKREDITAN RAKYAT (Studi Empiris pada Bank Prekreditan Rakyat di Tangerang) - Amalia Indah Fitriana; Hendra Galuh Febrianto (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The objective of this research is to analyze BPR liquidity risk management in Tangerang through asset management, leverage and capital adequacy with the final goal of recommending policy to improve BPR liquidity risk management. This type of research uses explanatory research type with quantitative approach. Analysis of data in research using multiple linear regression analysis in panel of financial report data 49 BPR in Tangerang from 2012 until 2016. There are two groups of variables used in this research. The dependent variable in this research is liquidity risk measured by current ratio. The independent variable in this research is asset management measured by total asset turnover, leverage measured with debt to equity ratio and capital adequacy measured by capital adequacy ratio. The results of this study indicate that three hypotheses partially have no effect. But the simultaneous test shows the three variables together have a negative and significant effect.